Effects of fundamentals on the exchange rate: A panel analysis for a sample of industrialised and emerging economies - José Eduardo de A. Ferreira (University of Kent, Department of Economics, 2006)
This paper tests the traditional monetary model of exchange rates for a sample of industrialized and emerging market economies by making use of panel techniques that allow for a high degree of heterogeneity across countries. The results demonstrated partial support for the monetary model for industrialised market economies but not for emerging ones. This constitutes a puzzle as it would expect countries with greater monetary instability to show a stronger association between exchange rates and monetary fundamentals.
Keywords: F31; F37; F41; 330; Foreign Exchange; Fundamentals; Panel Data; Unit Roots; Assets